Systematic review and meta-analysis on proximal-to-distal sequencing in team handball: Prospects for talent detection? - Serrien, B.; Baeyens, J.-P. (Journal of Human Kinetics, 2018)
The proximal-to-distal sequence has previously been discussed in the light of performance and injury prevention. Sports biomechanics literature in general, and in team handball in specific, has claimed to be of importance to inform coaches on what constitutes a `good` technical performance. However, hitherto no prospective studies exist on how this information may be used and this may in part be due to the general small sample sizes. We therefore performed a systematic review and meta-analysis of proximal-to-distal sequencing in team handball throwing motions. A total of fourteen articles were included in the systematic review. Meta-analyses were performed for the timing of maximal angles and angular velocities as well as initiation of joint angular velocities in the penalty throw, the standing throw with run-up and the jump shot of experienced team handball players. For the initiation of joint angular velocities, the overall sequence was estimated to start with pelvis rotation, followed by trunk rotation, trunk flexion, shoulder internal rotation and elbow extension. For maximal velocities, the sequence started with pelvis rotation, followed by trunk rotation, trunk flexion, elbow extension, and shoulder internal rotation (post ball release). The obtained results were discussed in the light of talent identification purposes. Limitations to individual study methodology and of the present meta-analysis were also discussed. Much more research will be necessary, but at the very least, this review can provide a starting point for evidence-based discussions between movement scientists and team handball coaches to include proximal-to-distal sequencing as a measure of coordination to gauge early onset of talent.